2010
DOI: 10.1507/endocrj.k10e-231
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell dysfunction and its clinical significance in gestational diabetes

Abstract: Pancreatic beta cells compensate for changes in whole body insulin sensitivity through an increase in insulin secretion. The relationship between insulin sensitivity and insulin secretion is characterized by a rectangular hyperbolic function, such that the product of the two variables, termed as the disposition index, should yield a constant for a given degree of glucose tolerance [1][2]. Although beta cell dysfunction and insulin resistance may occur independently, the disposition index typically decreases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 18 publications
2
46
2
2
Order By: Relevance
“…The patients who developed GDM in the 3rd trimester also had significantly higher HOMA-IR, which emphasizes the role of increased insulin resistance against the background of enormous tissue insulin demands in the development of late-onset GDM. Our findings are consistent with the results of other studies (44,45,46) showing unchanged AUC Ins /AUC Glu index, but an inadequate insulin compensation for decreased insulin sensitivity in women with GDM. We should also mention that the number of patients with a normal OGTT result at the 1st visit, but later diagnosed as having GDM, was much higher than expected.…”
Section: Discussionsupporting
confidence: 93%
“…The patients who developed GDM in the 3rd trimester also had significantly higher HOMA-IR, which emphasizes the role of increased insulin resistance against the background of enormous tissue insulin demands in the development of late-onset GDM. Our findings are consistent with the results of other studies (44,45,46) showing unchanged AUC Ins /AUC Glu index, but an inadequate insulin compensation for decreased insulin sensitivity in women with GDM. We should also mention that the number of patients with a normal OGTT result at the 1st visit, but later diagnosed as having GDM, was much higher than expected.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to beta cell function, levels of ISSI-2 in women with 2/3-AV were significantly lower than those with 1-AV. The level of beta cell function is associated with the severity of glucose intolerance in GDM [9]. Additionally, our previous investigation demonstrated that beta cell dysfuntion in women with 2/3-AV appeared more severe than those with 1-AV [10].…”
Section: Discussionmentioning
confidence: 86%
“…It is well known that an impaired insulin secretion plays a critical role in the development of T2DM or GDM in east Asian including Japanese [24,25]. Therefore, most of SNPs analyzed were insulin secretion candidate SNPs.…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%